Steroidal alkaloids defence metabolism and plant growth are modulated by the joint action of gibberellin and jasmonate signalling - Panda, Sayantan; Jozwiak, Adam; Sonawane, Prashant D.; Szymanski, Jedrzej; Kazachkova, Yana; Vainer, Andrii; Kilambi, Himabindu Vasuki; Almekias-Siegl, Efrat; Dikaya, Varvara; Bocobza, Samuel; Shohat, Hagai; Meir, Sagit; et al. (New Phytologist, 2022)
Steroidal glycoalkaloids (SGAs) are protective metabolites constitutively produced by Solanaceae species. Genes and enzymes generating the vast structural diversity of SGAs have been largely identified. Yet, mechanisms of hormone pathways coordinating defence (jasmonate; JA) and growth (gibberellin; GA) controlling SGAs metabolism remain unclear. We used tomato to decipher the hormonal regulation of SGAs metabolism during growth vs defence tradeoff. This was performed by genetic and biochemical characterisation of different JA and GA pathways components, coupled with in vitro experiments to elucidate the crosstalk between these hormone pathways mediating SGAs metabolism. We discovered that reduced active JA results in decreased SGA production, while low levels of GA or its receptor led to elevated SGA accumulation. We showed that MYC1 and MYC2 transcription factors mediate the JA/GA crosstalk by transcriptional activation of SGA biosynthesis and GA catabolism genes. Furthermore, MYC1 and MYC2 transcriptionally regulate the GA signalling suppressor DELLA that by itself interferes in JA-mediated SGA control by modulating MYC activity through protein-protein interaction. Chemical and fungal pathogen treatments reinforced the concept of JA/GA crosstalk during SGA metabolism. These findings revealed the mechanism of JA/GA interplay in SGA biosynthesis to balance the cost of chemical defence with growth.
Keywords: alpha-tomatine; defence; gibberellin (GA); growth; jasmonate (JA); steroidal glycoalkaloids (SGAs); Tomato

Steroidal scaffold decorations in Solanum alkaloid biosynthesis - Lucier, Rosalind; Kamileen, Mohamed O.; Nakamura, Yoko; Serediuk, Sofiia; Barbole, Ranjit; Wurlitzer, Jens; Kunert, Maritta; Heinicke, Sarah; O'Connor, Sarah E.; Sonawane, Prashant D. (Molecular Plant, 2024)
Steroidal glycoalkaloids (SGAs) are specialized metabolites produced by hundreds of Solanum species, including important vegetable crops such as tomato, potato, and eggplant. Although it has been known that SGAs play important roles in defense in plants and ``anti-nutritional''effects (e.g., toxicity and bitterness) to humans, many of these molecules have documented anti-cancer, anti-microbial, antiinflammatory, anti-viral, and anti-pyretic activities. Among these, a-solasonine and a-solamargine isolated from black nightshade (Solanum nigrum) are reported to have potent anti-tumor, anti-proliferative, and anti-inflammatory activities. Notably, a-solasonine and a-solamargine, along with the core steroidal aglycone solasodine, are the most widespread SGAs produced among the Solanum plants. However, it is still unknown how plants synthesize these bioactive steroidal molecules. Through comparative metabolomictranscriptome-guided approach, biosynthetic logic, combinatorial expression in Nicotiana benthamiana, and functional recombinant enzyme assays, here we report the discovery of 12 enzymes from S. nigrum that converts the starting cholesterol precursor to solasodine aglycone, and the downstream a-solasonine, a-solamargine, and malonyl-solamargine SGA products. We further identified six enzymes from cultivated eggplant that catalyze the production of a-solasonine, a-solamargine, and malonyl-solamargine SGAs from solasodine aglycone via glycosylation and atypical malonylation decorations. Our work provides the gene tool box and platform for engineering the production of high-value, steroidal bioactive molecules in heterologous hosts using synthetic biology.
Keywords: a-solamargine; Biosynthetic pathway; malonyl-solamargine; Solanum; Specialized metabolites; steroidal glycoalkaloids